A randomized controlled study of acupuncture for pain relief during first trimester surgical termination of pregnancy performed under local analgesia. Issue 3 (June 2022) - Ng, Dorothy Yuet Tao; Lo, Alexandra; So, Emily Wing Sze; Wong, Grace Ching Yin; Li, Raymond Hang Wun; Wong, Yu Yeuk; Ng, Ernest Hung Yu
Background: Acupuncture reduces pain levels in many painful conditions. This study compared pain levels during surgical termination of first trimester pregnancy by suction evacuation (SE) under local analgesia with and without the use of acupuncture. Methods: In all, 60 nulliparous women undergoing SE before 10 weeks of gestation were randomly assigned into one of the following three groups in a 1:1:1 ratio according to a computer-generated randomization list. In the control group, women received oral diazepam 5 mg and intramuscular (i.m.) injection of pethidine 30 and 15 min, respectively, prior to SE. In the acupuncture group, women received acupuncture 10 min before SE until the end of SE while oral diazepam 5 mg and i.m. injection of normal saline were given. In the combined group, women received acupuncture in addition to the drugs in the control group. Data from 52 participants were analysed. Pain scores during and after SE, post-operative side-effects and satisfaction levels were compared. Results: The three groups had similar baseline characteristics. The median pain levels during SE differed significantly between the control, acupuncture, and combined groups (80, 50 and 66 mm, respectively, p = 0.03). Pain levels during SE in the acupuncture and combined groups were significantly lower than that of the control group. However, the anxiety scores did not differ between the three groups after SE (p = 0.86). Conclusion: Acupuncture can provide additional benefit in terms of pain relief in women undergoing first trimester termination of pregnancy by SE under local analgesia.